Application and control of flexible alternating current transmission system devices for voltage stability enhancement of renewable-integrated power grid: A comprehensive review. Issue 3 (March 2021) - Adetokun, Bukola Babatunde; Muriithi, Christopher Maina
Abstract: This paper presents a comprehensive review on the application and control of Flexible Alternating Current Transmission Systems (FACTS) devices in order to improve voltage stability of power grid with high share of renewable energy systems. The rise in the development of renewable energy technologies is driven by the attempts to mitigate the effects of global warming. In addition, global energy demand continues to rise as new electricity-driven systems such as electric vehicles are being developed and as remote locations are being connected to the grid. These changes in the power grid formation comes with attendant challenges which must be addressed. One of these challenges is voltage stability issues. This paper therefore explores the applications of FACTS devices for voltage stability improvement and points out the future research direction in the area of voltage stability enhancement by FACTS devices for modern power grids characterized by increasing levels of renewable energy penetration. Abstract : Control scheme; Grid integration; FACTS devices; Renewable energy; Voltage stability